Analisis Pendapatan Usahatani Kopi Robusta Pola Monokultur Pasca Kenaikan Harga Kopi Tahun 2024 (Study Kasus Desa Sukananti Kecamatan Way Tenong) - Aji Setiya Bakti; Sri Puji Lestari; Ungki Prabowo Putra; Zakiatun Nufus; Yansen Atik; Yuni Elmita Sari (AgriMalS, 2026)
The increase in coffee prices in 2024 is an opportunity for farmers to earn more income. Coffee farmers in Sukananti Village generally cultivate coffee monoculture. Monoculture planting patterns can provide higher incomes because farmers will be more focused on crops with monoculture patterns. The novelty and focus of the research conducted are to examine the income of coffee farmers with a monoculture system when coffee prices increase significantly in 2024. The study aims to determine the income and feasibility of robusta coffee farming in Sukananti Village, Way Tenong District, West Lampung Regency, after the price increase that occurred in 2024. The sample or respondents used in this study were 25% of the population of robusta coffee farmers, namely, 73 robusta coffee farmer respondents. The sample determination was carried out using the simple random sampling method or a simple random sampling technique. Data analysis used the structure of income and costs in farming. The results showed that income from coffee farming was Rp. 57,679,892.83 with a net income of Rp. 49,481,482.37. Per hectare/season/year. R/C ratio analysis based on cash costs and total costs of robusta coffee farming per hectare/year/season in Sukananti Village, Way Tenong District, West Lampung Regency, is valued at 13.74 and 7.04, where the value is > 1. This indicates that robusta coffee farming is very feasible to run.